Multi‐stack fuel cell efficiency enhancement based on thermal management. Issue 1 (1st March 2017) - Mohamed Ramadan, Haitham Saad; de Bortoli, Quentin; Becherif, Mohamed; Claude, Frederic
Abstract : Automotive manufacturers face serious difficulties concerning the expected fossil fuel depletion and the emitted pollutants during combustion. The fuel cell (FC) vehicle is considered a promising solution for greener and sustainable transportation. The integration of FC in vehicles is limited by some technological constraints and technical barriers which can be partially met by splitting the power and energy into different 'downsized' FCs named multi‐stack FCs. This study aims at proposing a multi‐stack FC configuration for electric vehicles (EVs) to minimise its start‐up time, heating/cooling and cycling problems. To properly reach such desired operating conditions, a novel thermal management technique is proposed. Using the modularity provided by multi‐stack solution, each FC is activated depending on the FCs temperature and the required vehicle power. Simulation results, using MTCSim © software, demonstrate the capability of the proposed thermal management approach to effectively enhance the EV's multi‐stack FC's life span, cycling and efficiency, besides optimising its operation performance.